Effect of Ventilation System on Spread and Control of Infections (COVID-19) in Indoor Environments: Based on Current Studies - Nourmohammadi, Mohammad; Mirzaei, Ramezan; Taban, Ebrahim; Yari, Saeed (Asian Pacific Journal of Environment and Cancer, 2020)
Transmission of infectious diseases like SARS-COV-2 by ventilation systems has become an international concern. In this study, an attempt was made to assess the role of ventilation systems in spread and control of SARS-COV-2 in indoor environments. the results showed that the ventilation system can play an important role in controlling and spreading infectious diseases in indoors environment air change per hour (ACH) is one of the most effective management and engineering strategy to reduce the risk of infection spread. It can be concluded that ventilation system can reduce and spread the infectious disease in indoor environments.